2016
DOI: 10.1037/pas0000147
|View full text |Cite
|
Sign up to set email alerts
|

Do neuropsychological test norms from African Americans in the United States generalize to a Zambian population?

Abstract: Healthy Zambian adults (N = 324) were evaluated to determine to what degree a Western neuropsychological (NP) test battery, with African American norms adjusted for age, gender, and education could be used in healthy Zambians, including 157 (48.46%) men and 167 (51.54%) women with an average age of 38.48 (SD = 12.80) years and an average education level of 11.02 (SD = 2.58) years. The NP battery included tests of attention/working memory, executive function, verbal fluency, processing speed, verbal and visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 38 publications
4
35
1
Order By: Relevance
“…However, the effects of “normal” age, education, and sex on the NC test performances were controlled for by using demographically corrected standard scores ( T -scores) generated with a previously collected 324 HIV− normative sample. 21 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the effects of “normal” age, education, and sex on the NC test performances were controlled for by using demographically corrected standard scores ( T -scores) generated with a previously collected 324 HIV− normative sample. 21 …”
Section: Resultsmentioning
confidence: 99%
“…Age range – All the participants were required to be between 20 and 65 years of age (to conform to the age range of the HIV− controls who participated in the Zambian NC norming study). 21 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important contribution of the rapidly growing field of cross cultural neuropsychology is determining the appropriateness of the use of western tests and norms across diverse cultural groups. While much of the work to date has been conducted on large ethnic minorities (e.g., Hispanic and African Americans), mainly in the United States (Andreotti & Hawkins, ; Flores et al, ; Manly et al, ; Manly, Byrd, Touradji, & Stern, ; Ostrosky‐Solís, López‐Arango, & Ardila, ; Pontón, Gonzalez, Hernandez, Herrera, & Higareda, ; Rosselli & Ardila, ), broader efforts have been undertaken internationally, including determining the validity of the use of American minority norms outside of the United States (e.g., Hestad et al, ), the development of norms across different countries that use the same language (e.g., Guardia‐Olmos, Pero‐Cebollero, Rivera, & Arango‐Lasprilla, ) and the development of norms for smaller ethnic minorities outside of the United States (e.g., Nielsen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review by Fasfous, Al-Joudi, Puente, and Perez-Garcia (2017) identified that, (Fasfous et al, 2017). Other efforts to develop normative standards outside of American and European cultures suggest comparability of the construct measured when normative standardizations and underlying issues of cultural validity are appropriately addressed (e.g., Zambia, Hestad et al, 2016, Kabula et al, 2017China, Gupta et al, 2014, Heaton et al, 2008, Shi et al, 2015Brazil, de Almeida, et al, 2013;India, Ghate et al, 2015, Kamat et al, 2012, Malda, van de Vijver, Srinivasan, Transler, & Sukumar, 2010Czech Republic, Bezdicek et al, 2012South Africa, Nell, 1999;Nell, Myers, Colvin, & Rees, 1994;Cameroon, Ruffieux, et al, 2010;South Korea, Ko, Rosen, Simpson, & Brown, 2014), although there are some exceptions (e.g., lexical fluency and block design in Cameroon, Ruffieux, et al, 2010).…”
Section: Cultural and International Considerationsmentioning
confidence: 99%